DESIGN AND CHARACTERIZATION OF HIGH-PERFORMANCE LAYERED CATHODE MATERIALS FOR SODIUM-ION BATTERIES - Rakhymbay, Lunara (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Sodium-ion batteries (SIBs) have garnered significant interest owing to their potential in advancing future energy storage technology. Nonetheless, a major limitation hindering their practical deployment is the insufficient performance of cathode materials, particularly Mn-based layered oxides, which undergo significant capacity deterioration caused by structural alterations during cycling. This thesis provides a comprehensive analysis of the structural and electrochemical properties of innovative layered oxides, focusing on doping methods to enhance their performance. An in-depth examination of the P3-Na0.62Mn0.75Cu0.19O2 material underscores the notable influence of partial doping with Cu on enhancing structural durability and electrochemical efficiency. Operando XRD analyses indicate that Cu-doping enhances the stability of the single-phase reaction and inhibits the unwanted P3-O3 phase transition throughout the cycling process. Moreover, operando DEMS verifies that there is no irreversible O2 gas evolution, highlighting the reversible oxygen redox stability P3-Na0.62Mn0.75Cu0.19O2. XANES studies, complemented by XPS, reveal the active participation of Cu2+/Cu3+, Mn3+/Mn4+, and O2-/On- redox pairs, leading to a remarkable discharge capacity of 212.2 mAh g-1 (0.79 Na+). Alongside P3-Na0.62Mn0.75Cu0.19O2 the present dissertation delves into the synthesis and characterization of a series of Nax(Ni–Fe–Mn)O2 cathode materials, specifically focusing on varying sodium content (x = 0.75, 0.85, and 0.95). The Na0.95Mn0.4Fe0.25Ni0.35O2 cathode material demonstrated exceptional electrochemical performance exhibited 175.7 mAh g-1 and with 77% capacity retention after 100 cycles. The findings indicate that optimizing sodium content significantly lowers charge transfer resistance and improves Na⁺ ion diffusion kinetics. Operando XRD validated the reversible O3–P3 phase transitions, demonstrating no irreversible structural degradation, while in situ Mössbauer spectroscopy offered valuable insights into the iron redox behavior at elevated voltages, which observed quick oxidation process to 4+. This study shows that Cu-doping and precise composition tuning are key to improving oxygen redox activity and structural stability in Mn-based layered oxides. The progress made in this area leads to improved cycling stability, increased energy density, and the possibility of commercializing sodium-ion batteries, setting the stage for sustainable and efficient energy storage options.
Keywords: layered type; anionic-redox; doping; high capacity; cathode; type of access: embargo